EFFECT OF STARTING POWDER PREMIXING ON THE INTERPHASE EXCHANGE COUPLING IN Nd₂Fe₁₄B + 10 WT % Fe NANOCOMPOSITES OBTAINED TROUGH MECHANICAL MILLING - HIRIAN, R.; MICAN, S.; ISNARD, O.; BARBU, L.; POP, V. (Studia Universitatis Babeș-Bolyai Physica, 2016)
In the frame of optimizing the potential, of had /soft nanocomposites for high performance applications, we report on the effect of starting powder premixing on the structure, microstructure and exchange coupling in hard/soft magnetic phases. Nd2Fe14B powder was first mixed with Fe powder using two different means: by hand or by using a Turbula Mixer. Moreover, in the hand mixed powders the Fe particle size was changed from 100 to 1 μm, while the samples mixed using the Turbula Mixer contained only Fe particles of around 1 μm in size. The mixed powders were subsequently milled for 6 hours in a planetary ball mill; the calculated impact energy was 77 mJ/impact and 10 kJ/g for the entire duration of process. Good exchange coupling was obtained in all three cases. The samples prepared with Fe < 1 μm particles yielding slightly better results due to better dispersion of the two phases in the final nanocomposite material. The highest energy product was achieved for the sample premixed with the Turbula Mixer ((BH)max=125 kJ/m3) after being annealed at 800 °C for 1.5 min.